Parameterization through Geometry Capture - Bandler, John W. (Bandler Corporation, 1998)
Presentation addressed the critical issue of parameterization of geometrical structures for the purpose of layout-based design, in particular automated EM optimization using HP HFSS.
Slides for a presentation given by John W. Bandler.
Keywords: optimization; automated EM optimization